Konsep Skematik Desain pada Perencanaan dan Perancangan Sekolah Barista dan Kedai Kopi di Desa Wanagiri dengan Tema Arsitektur Organik - Paramisiwi, Putu Pritayuni; Sastrawan, I Wayan Wirya; Prabawa, Made Suryanatha (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Coffee is one of the ingredients of food or drink that we often encounter and even become one of the daily needs of the community. Coffee plants grow optimally throughout Bali at an altitude of 800-1500 meters above sea level which has a rainfall of around 2000-3000 mm/year with an optimal temperature of around 21-24 degrees Celsius. Wanagiri Village is one of the places where coffee plants grow, especially Arabica coffee in Bali. Behind the good quality of Balinese coffee, of course, it takes a reliable and experienced barista to mix the coffee drink in order to produce processed with very good quality for consumption. The existence of a barista is currently the main point in the success of a coffee shop in Bali. Currently, quite a lot of coffee shops are bankrupt due to their products being processed incorrectly, this is due to the knowledge of the baristas who are not good or just learning the self-taught way. The availability of barista school facilities and coffee shops can reduce existing problems, the design is carried out by responding to problems regarding coffee baristas by thinking about and creating learning space and facilities that are comfortable, clean, and can attract the attention and interest of the barista or the community to visit as well as to undergo education baristas and educate the public about coffee for economic and environmental sustainability